2016
DOI: 10.1007/s11103-016-0552-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating QTL mapping and transcriptomics identifies candidate genes underlying QTLs associated with soybean tolerance to low-phosphorus stress

Abstract: Soybean is a high phosphorus (P) demand species that is sensitive to low-P stress. Although many quantitative trait loci (QTL) for P efficiency have been identified in soybean, but few of these have been cloned and agriculturally applied mainly due to various limitations on identifying suitable P efficiency candidate genes. Here, we combined QTL mapping, transcriptome profiling, and plant transformation to identify candidate genes underlying QTLs associated with low-P tolerance and response mechanisms to low-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 51 publications
3
65
0
Order By: Relevance
“…The sustainability of the use of P fertilizers to optimize crop yields is in jeopardy due to the crisis of the global reserve of rock phosphate and P pollution. Compared with other crop species, soybean needs more P for growth and development; thus, low-P (LP) stress has become a major factor limiting soybean production [2]. Therefore, elucidating the response and adaptation mechanism of soybean to LP stress is of great urgency and importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sustainability of the use of P fertilizers to optimize crop yields is in jeopardy due to the crisis of the global reserve of rock phosphate and P pollution. Compared with other crop species, soybean needs more P for growth and development; thus, low-P (LP) stress has become a major factor limiting soybean production [2]. Therefore, elucidating the response and adaptation mechanism of soybean to LP stress is of great urgency and importance.…”
mentioning
confidence: 99%
“…Using genome-wide high-throughput RNA sequencing (RNA-seq) technology, we then identified all circRNAs in the roots of soybean seedlings and validated them by real-time PCR. Our study specifically (1) identified and characterized soybean root circRNAs that are responsive to LP stress; (2) identified and characterized the possible roles of the cir-cRNA-host genes of differentially expressed (DE) circRNAs in regulating soybean tolerance to LP stress via Gene Ontology (GO) enrichment analysis; and (3) predicted and discussed the sponge action of DE circRNAs and miRNA-targeted genes.…”
mentioning
confidence: 99%
“…The sequencing and preprocessing results are summarized in Table 1. An initial comparative analysis of the transcriptome dataset has revealed that acid phosphatases might be involved in enhancing P efficiency in low-P tolerance in soybean, and gene expression analysis and functional analysis has indicated the robustness of the dataset [11]. However, further analyses using the data is needed-for example, identifying the underlying alternative splicing genes and regulatory network as well as identifying the differentially expressed genes systemically involved in low-P tolerance in roots and leaves-which will further improve our comprehensive understanding of the molecular mechanism underlying plant adaptations to phosphate deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean treatment for phosphorus-deficient and -sufficient conditions were followed as previously described [5,11]. Briefly, seeds were surface-sterilized with 0.5% sodium hypochlorite for no more than 4 minutes, rinsed twice with sterile water, and then germinated in sterile vermiculite.…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
“…The combination of quantitative genetics and co‐expression studies provides a powerful framework for functional characterization of genes (Mackay et al ., ). For instance, this strategy has been used to identify genes controlling glucosinolates and anti‐herbivore defense in Arabidopsis (Chan et al ., ), micronutrients in chickpea (Upadhyaya et al ., ), leaf morphology in oilseed rape (Jian et al ., ) and phosphorus stress tolerance in soybean (Zhang et al ., ). In this class of approaches, one may utilize a single data set to determine loci associated with a trait of interest and then narrow down the search to those whose respective gene transcripts are correlated with the trait (Chen et al ., ); moreover, streamlining the list can be carried out by investigation of gene co‐expression based on publically available data sets (Serin et al ., ).…”
Section: Introductionmentioning
confidence: 97%